TINJAUAN YURIDIS ATAS TUGAS-TUGAS NOTARIS SEBELUM PELAKSANAAN PERJANJIAN KREDIT DI PERBANKAN - HISKIA MEIKO AUNAMULA PANGGABEAN (PREMISE LAW JURNAL, 2015)
Nowadays, notarial profession develops rapidly which indicates that it is highly needed by the Indonesian people. Not only individuals, but also corporations need Notaries’ services. One of the corporations is banking financial institution. In its management, a Bank needs a Notary for giving legal certainty to its debtors and to the Bank itself; it means that a Notary becomes a Bank’s partner. In the regulation on a Notary’s duty and authority as it is stipulated in Law No. 2/2014 on the Amendment of Law No. 30/2004 on the Regulation of Notaries Profession, states about the authority and automatically becomes the duty of a Notary in doing his profession. In order that the process of pre-credit contract and legal certainty can run smoothly, it is recommended that Notary should be able to examine and ask for all supporting documents from the parties concerned in order to obtain an administrative legal basis on whatever is needed to make a complete credit contract a law which can be obeyed by both parties with the minimum legal loophole or even to be eliminated. Keywords: Judicial Review, Implementation of Notary’s Duty in Pre-Credit Contract